IMPACT OF INNOVATIVE TECHNOLOGIES ON THE MANAGEMENT FORMAT UNDER CONDITIONS OF SUSTAINABLE DEVELOPMENT - Тетяна Кулініч; Михайло Тарасюк; Світлана Микуланинець (Економіка та суспільство)
For modern management systems, the impact of radically new or improved technologies is becoming increasingly significant as they become key factors in the transformation of management. The outlined significance is because every social, ecological, or economic innovation is essentially an idea or product that changes the set of methods, techniques, tools, and management procedures, correcting or accelerating the evolution of the theory and practice of sustainable development. In this context, the format of sustainable development management is formed, which acts as a platform for broadcasting the innovative triune impact on the system of managing economic activities. Thus, the article aims to study the impact of innovative technologies on management format in the context of sustainable development. The research findings prove that the integration of innovative technologies into management is carried out through the main management functions, which creates opportunities to adjust and optimize resource use in response to changing ecological, social, and economic conditions.